The Effect of Personal Competence, Emotional Stability, and Intrinsic Motivation on Teacher Work Commitment - Abdi, Wuri Tamtama; Wijaya, Candra; Ananda, Rusydi (Pascasarjana Universitas KH. Abdul Chalim, 2024)
The issue of work commitment is the basis of this study, examined through the lens of emotional stability, intrinsic motivation, and self-competence. The main purpose of this study is to explain the interaction between a person's emotional stability and their intrinsic motivation, as well as the teacher's competence towards the teacher's work commitment. This study uses a quantitative approach using ex post facto methodology. The research population was one hundred and ninety-one teachers from three different Madrasah Aliyah in Medan City. A questionnaire with a Likert scale was used to collect data. Using route analysis tools, research hypotheses are evaluated. The research results show: